Lipophagy and Alcohol-Induced Fatty Liver - Li Yang; Changqing Yang; Paul G. Thomes; Paul G. Thomes; Kusum K. Kharbanda; Kusum K. Kharbanda; Carol A. Casey; Carol A. Casey; Mark A. McNiven; Terrence M. Donohue; Terrence M. Donohue (Frontiers Media S.A., 2019)
This review describes the influence of ethanol consumption on hepatic lipophagy, a selective form of autophagy during which fat-storing organelles known as lipid droplets (LDs) are degraded in lysosomes. During classical autophagy, also known as macroautophagy, all forms of macromolecules and organelles are sequestered in autophagosomes, which, with their cargo, fuse with lysosomes, forming autolysosomes in which the cargo is degraded. It is well established that excessive drinking accelerates intrahepatic lipid biosynthesis, enhances uptake of fatty acids by the liver from the plasma and impairs hepatic secretion of lipoproteins. All the latter contribute to alcohol-induced fatty liver (steatosis). Here, our principal focus is on lipid catabolism, specifically the impact of excessive ethanol consumption on lipophagy, which significantly influences the pathogenesis alcohol-induced steatosis. We review findings, which demonstrate that chronic ethanol consumption retards lipophagy, thereby exacerbating steatosis. This is important for two reasons: (1) Unlike adipose tissue, the liver is considered a fat-burning, not a fat-storing organ. Thus, under normal conditions, lipophagy in hepatocytes actively prevents lipid droplet accumulation, thereby maintaining lipostasis; (2) Chronic alcohol consumption subverts this fat-burning function by slowing lipophagy while accelerating lipogenesis, both contributing to fatty liver. Steatosis was formerly regarded as a benign consequence of heavy drinking. It is now recognized as the "first hit" in the spectrum of alcohol-induced pathologies that, with continued drinking, progresses to more advanced liver disease, liver failure, and/or liver cancer. Complete lipid droplet breakdown requires that LDs be digested to release their high-energy cargo, consisting principally of cholesteryl esters and triacylglycerols (triglycerides). These subsequently undergo lipolysis, yielding free fatty acids that are oxidized in mitochondria to generate energy. Our review will describe recent findings on the role of lipophagy in LD catabolism, how continuous heavy alcohol consumption affects this process, and the putative mechanism(s) by which this occurs.